Konsekuensi Yuridis Perubahan Obyek Hak Tanggungan dalam Akad Pembiayaan Mudharabah - Septi Kurniawati (Universitas Islam Indonesia, 2018)
Mudharabah is a partnership contract in business sector where the results will be divided in half. Mudharabah does not use collateral, guarantees are requested if the mudharib (debtor) is feared to be incapable to fulfill its performance. If mudharib fails to pay, then the execution can be carried out as compensation which is the right of Shobibul Maal (creditor). In this paper there are two problems: what must be done to change an object on the mortgage right and the consequences; and what if it is linked using a mudharabah agreement. This research is normative, in which the data is obtained from laws, literature, electronic media and through analysis of the Supreme Court's Decision which is then analyzed as a whole qualitatively. Decision of the Supreme Court No. 410K/Ag/2014 states that the Deed that has been signed and agreed with the conscious has absolute legal force that cannot be canceled for any reason. The change of an object in the Underwriting Right with a Mudharabah agreement has consequences for permanent or binding legal force on the parties. This was proven in the Supreme Court Decree No. 410K/Ag/2014 that the change of object in the Mortgage Rights with the Mudharabah agreement was justified by the Judge.